Relationships between biomarkers of inflammation, ovarian steroids, and age at menarche in a rural polish sample. Issue 3 (20th April 2013) - Clancy, Kathryn B.H.; Klein, Laura D.; Ziomkiewicz, Anna; Nenko, Ilona; Jasienska, Grazyna; Bribiescas, Richard G.
<x xml:space="preserve">Abstract</x> Objectives To test the hypothesis that life history trade‐offs between maintenance and reproductive effort would be evident through inverse associations between levels of a biomarker of inflammation [C‐reactive protein (CRP)], and ovarian hormones. Associations between CRP and age at menarche were also explored. Methods Urinary CRP, salivary progesterone, and estradiol were measured over one menstrual cycle from rural Polish women (n = 25), representing a natural fertility sample. Age of menarche was assessed through interview recall methods. We used minimum second‐order Akaike Information Criteria as a means of multiple regression model selection, and repeated measures ANOVA to test cycle‐dependent hypotheses. Results Comparisons of individuals in high and low CRP tertiles revealed that those with high CRP had significantly lower progesterone (luteal P = 0.03, mid luteal P = 0.007) but not estradiol (follicular P = 0.21, luteal P = 0.15) concentrations through the menstrual cycle. However, when the age at menarche was included in the analysis, both age at menarche and urinary CRP were negatively associated with estradiol (R2 = 0.44, P = 0.0007). Age at menarche and estradiol were the strongest negative predictors of CRP (R2 = 0.52, P = 0.0001). Conclusions Inflammation itself may suppress ovarian function, or indicate immune challenges that lead to ovarian suppression. The timing of menarche may also influence adult inflammatory sensitivity and ovarian hormone concentrations. This lends support to existing models of trade‐offs between maintenance and reproduction in women. Am. J. Hum. Biol. 25:389–398, 2013. © 2013 Wiley Periodicals, Inc.